Web Based Geographic Information System for Advertising Management in Mataram City - Boy Arista; Moh. Ali Albar; Ariyan Zubaidi (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2020)
The city of Mataram has not yet implemented a geographical information system regarding ad management in the city of Mataram. This makes it difficult for people to find information about billboards in the city of Mataram. The purpose of this research is to build a system that can provide information about locations, reservations and help the public to find out the distribution point of billboards in the city of Mataram. This system was developed by the Codeigniter Framework and uses the PHP and HTML programming languages, and also uses the Google Map API to display billboards. In this study using the waterfall method as the life cycle of system development. We use blackboxes and MOS (Mean Opinion Score) as system testing. The results of testing the black box function in the system are running well without errors. Based on the questionnaire that has been distributed, this system makes it easy for admins to enter billboard data in the city of Mataram with the results of the questionnaire strongly agree and agree as much as 96%. The questionnaire about the performance of this system from the user's side to find out and order a billboard in the city of Mataram with the results of the questionnaire strongly agreed and agreed as much as 94%. therefore, this system is feasible to use.